The Studies on Women in al-Andalus. A State of Affairs - Boloix Gallardo, Bárbara (Anaquel de Estudios Árabes, 2021)
The study of the women in al-Andalus constitutes a subject which has generated a growing multidisciplinary scientific interest, as it has been developed not only within the Arabic Studies but also in other branches of Humanities and Social Sciences in both the national and the international academic world. Being conscious of the numerous bibliography that this field has produced, the present article aims to offer an updated state of affairs of the main studies devoted to this matter. It tracks its historiographical roots in the 19th century and follows, from the perspective of the content and methodology, both the development of this studies throughout the 20th century and their consolidation in the 21st. This article also intends to identify the weak points of this subject that need to be reinforced in future publications. With this review, we intend to offer a useful reference guide that could orientate those researchers interested in this line of research.